Lietuviškų knygų rinkinys Britų bibliotekoje (tęsinys) - Navickienė, Aušra; Zmrozek, Janet (Knygotyra, 1997)
Lithuanian books are part of the broader collection of books in Slavonic and other languages of Eastern Europe at the British Library. In this article, the authors present the results of the latest investigation of the collection, which contains unique copies of books very important for Lithuanian culture. The aim of the investigation was to examine Lithuanian books published between 1547 and 1904 and to clarify the history of this collection. In total, 229 copies of Lithuanian printings and 23 old Lithuanian texts in foreign language books have been identified. During the investigation, data about each book were gathered and analyzed. The studied books are presented in an alphabetical list. This article provides a continuation of the list, which contains descriptions of 175 Lithuanian books from 1865 to 1904. The first part of the list, titled "The Descriptions of Lithuanian Books and Old Lithuanian Texts in Foreign Language Books of 1547-1864 at the British Library," along with the article, was published in volume 25(32) of "Knygotyra." The list includes abridged bibliographical descriptions, the British Library’s signatures, information on physical condition, marks of books, information about the sources of acquisition (date of acquisition, sources, and method of acquisition), and bibliographical sources and literature related to the book.